Apatite and monazite: An effective duo to unravel superimposed fluid-flow and deformation events in reactivated shear zones - Prent, Alexander; Beinlich, Andreas; Raimondo, T.; Kirkland, Chris; Evans, Noreen; Putnis, Andrew (ELSEVIER, 2020)
Mylonitic shear zones crosscutting homogenous granitoids can retain evidence of fluid-driven metasomatic retrogression and reactivation. However, the relationships between fluid-rock interaction, retrogression, deformation and mylonitisation, and the timing thereof, are often cryptically recorded. This study focuses on the granulite-facies Boothby Orthogneiss from the Reynolds Range, central Australia, which contains a large scale mylonitic shear zone with an apparent record of structural inheritance, fluid infiltration and reactivation. The chosen site provides an ideal natural laboratory in which to investigate the timing of deformation, associated fluid flow and mass transport. U–Pb isotope analyses of monazite indicate an average Pb recrystallization age of c. 1560 Ma, demonstrating that the orthogneiss fabric developed during the Mesoproterozoic Chewings Orogeny (1590–1550 Ma). Structural mapping suggests that this shear zone represents a Riedel branch of larger structures that were subsequently reactivated during the Paleozoic Alice Springs Orogeny (450–300 Ma). The timing of reactivation and fluid flow is constrained by U–Pb dating of apatite, which is present as a stable U-bearing mineral in both orthogneiss and mylonite. Modelling of apatite radiogenic-Pb retention ages, accounting for a wide potential range in common Pb compositions, demonstrates at least some growth and/or recrystallization at c. 1500 Ma and c. 400 Ma, confirming apatite precipitation during Alice Springs shearing and the reactivation of Chewings-age structures. In addition, Alice Springs-aged apatite is found along pre-existing fabrics in the orthogneiss in the vicinity of the shear zone, indicating pre-kinematic fluid flow across the shear zone boundary and into country rock that was otherwise largely unaffected. The combined datasets demonstrates that integrated apatite and monazite U–Pb geochronology is an effective method to unravel the record of superimposed fluid-flow and deformation events. This includes the detection of an ‘inverse younging relationship’, where younger ages are preferentially recorded in the wall rock as rather than in the reactivated shear zone. Such effects are potentially common where deformation is driven by pre-kinematic fluid-rock interaction, with subsequent deformation enhancing the removal of replacement assemblages in more deformed rocks and favouring their preservation in less deformed rocks.